The Embodied Child Readings in Children's Literature and Culture - Harde, Roxanne; Kokkola, Lydia (Children's Literature and Culture, 2018)
The Embodied Child: Readings in Children's Literature and Culture brings together essays that offer compelling analyses of children's bodies as they read and are read, as they interact with literature and other cultural artifacts, and as they are constructed in literature and popular culture. The chapters examine the ideology behind the cultural constructions of the child's body and the impact they have on society, and how the child's body becomes a carrier of cultural ideology within the cultural imagination. They also consider the portrayal of children's bodies in terms of the seeming dichotomies between healthy-vs-unhealthy bodies as well as able-bodied-vs-disabled, and examines flesh-and-blood bodies that engage with literary texts and other media. The contributors bring perspectives from anthropology, communication, education, literary criticism, cultural studies, philosophy, physical education, and religious studies. With wide and astute coverage of disparate literary and cultural texts, and lively scholarly discussions in the introductions to the collection and to each section, this book makes a long-needed contribution to discussions of the body and the child.